Effect of streptococcal arginine deiminase on the function of CD4+ and CD8+T lymphocytes - E. A. Starikova; J. T. Mammedova; A. Ozhiganova; A. M. Lebedeva; T. A. Leveshko; L. A. Burova; I. V. Kudryavtsev (Медицинская иммунология, 2024)
Arginine metabolism plays an important role in regulating the functions of immune cells in mammals. Pathogenic microbes use the mechanism of arginine depletion to suppress the immune response during infection. Arginine deiminase is a microbial arginine-hydrolyzing enzyme important for survival at low pH in the focus of infection, or in phagolysosomes, as well as under low-glucose conditions. The effect of bacterial arginine deiminase on the functions of adaptive immune cells remains poorly understood. The aim of our study was to evaluate the effect of streptococcal arginine deiminase on the proliferation and autophagy of CD4+ and CD8+ human peripheral blood T lymphocytes.The enzyme effects were studied with supernates of ultrasonic lysates from parental Streptococcus pyogenes M49-16, and its isogenic mutant with inactivated arcA gene (Streptococcus pyogenes M49-16delarcA). The study was performed with blood samples of healthy donors. The fraction of mononuclear leukocytes was isolated by centrifugation in a Ficoll density gradient. To evaluate proliferation levels, a method based on the staining of intracellular proteins with vital fluorescent dye carboxyfluorescein succinimidyl ester (CFSE) was used. The level of autophagy was studied using the fluorescent Lysotracker Green DND-26 dye. To analyze the proliferation and autophagy of T helper cells (CD3+CD4+) and cytotoxic T lymphocytes (CD3+CD4-), the obtained cell suspensions were stained with antibodies against CD4, CD45RA, and CD3. The proportion of necrotic cells was determined by staining with a fluorescent DNA-binding DAPI dye. The normality of the distribution was assessed by Shapiro–Wilk test. The data were analyzed using Kruskal–Wallis criterion, followed by Mann–Whitney criterion for pairwise comparisons and expressed as median and interquartile ranges (Q0.25-Q0.75).When comparing the effects of supernatants from the parental and mutant streptococcal strains, which differed in expression of arginine deiminase gene, we have shown that the bacterial enzyme had no effect on the functions of inactive lymphocytes. However, streptococcal arginine deiminase completely suppressed proliferation of CD4+ and CD8+T lymphocytes stimulated with anti-CD2/CD3/CD28 antibodies. These effects were accompanied by a decrease in the autophagy levels. At the same time, arginine deiminase did not exert cytotoxic effects upon lymphocytes. L-arginine applied at the doses exceeding physiological levels caused restoration of the cellular functions. There were no differences between the studied parameters of CD4+ and CD8+T lymphocyte subsets.The obtained data show that the antiproliferative effect of arginine demimnase may be associated with ability of the enzyme to inhibit autophagy and confirm an opportunity of the bacterial enzyme to suppress host adaptive immune responses.